Penyuluhan tentang Hukum Adat Kawin Lari pada Ibu-Ibu Pengajian - Kartika Sari, Fitri; Fachrul Aljamili, Muhammad (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2024)
Counseling on elopement customary law to women in Sungai Piul, Bangko Hamlet Village aims to increase public understanding of marriage arrangements in customary law and its legal implications. Elopement, as a growing tradition in some communities, is often faced with legal challenges, both state and customary law. This counseling targeted women because they play an important role in disseminating information to their families and the surrounding community. This counseling program includes an explanation of the basis of customary law, social impacts, and how to solve elopement problems from the perspective of Islamic law and state law. With an approach based on interactive dialogue, participants are given the opportunity to ask questions and discuss, thereby creating a deeper understanding of the importance of respect for applicable laws. The results of this activity are expected to be able to contribute positively to increasing legal awareness among the local community and can reduce the potential for abuse of elopement traditions.